2021
DOI: 10.1371/journal.pone.0254834
|View full text |Cite
|
Sign up to set email alerts
|

A phenolic-rich extract from Ugni molinae berries reduces abnormal protein aggregation in a cellular model of Huntington’s disease

Abstract: Accumulation of misfolded proteins in the brain is a common hallmark of most age-related neurodegenerative diseases. Previous studies from our group identified the presence of anti-inflammatory and antioxidant compounds in leaves derived from the Chilean berry Ugni molinae (murtilla), in addition to show a potent anti-aggregation activity in models of Alzheimer´s disease. However, possible beneficial effects of berry extracts of murtilla was not investigated. Here we evaluated the efficacy of fruit extracts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In recent years, researches have confirmed the beneficial effects of flavonoids to health, including their use in conditions related to autophagy, such as neurodegenerative diseases ( Dai et al, 2021a ; Pérez-Arancibia et al, 2021 ). A large number of experiments have shown that flavonoids and its derivatives can improve chondrocytes and thus combat against OA, which makes it possible to apply flavonoids in clinical studies ( Basu et al, 2018 ; Ansari et al, 2020 ).…”
Section: Phytochemicals For the Treatment Of Oa By Promoting Autophagymentioning
confidence: 99%
“…In recent years, researches have confirmed the beneficial effects of flavonoids to health, including their use in conditions related to autophagy, such as neurodegenerative diseases ( Dai et al, 2021a ; Pérez-Arancibia et al, 2021 ). A large number of experiments have shown that flavonoids and its derivatives can improve chondrocytes and thus combat against OA, which makes it possible to apply flavonoids in clinical studies ( Basu et al, 2018 ; Ansari et al, 2020 ).…”
Section: Phytochemicals For the Treatment Of Oa By Promoting Autophagymentioning
confidence: 99%
“…Arancibia et al discovered that extracts (phenolic rich) from murtilla berries of the 19-1 genotype significantly decreased peptide (polyglutamine) accumulation amounts, corresponding with the regulation in the expression patterns of proteins, which are related to autophagy and thus promising in HD therapy. Berries were extracted by exhaustive maceration with increasing polarity solvents ( Pérez-Arancibia et al, 2021 ).…”
Section: Phytoconstituents In Different Neurological Disordersmentioning
confidence: 99%
“…Additionally, the models explore genetic pathways and mechanisms underlying disease development such as expansions, aberrant splicing, repeat-associated non-AUG (RAN) translation and RNA frameshifting. By using methods such as lentiviral transduction, microinjection with mRNA and transposase-mediated recombination, transgenic models were generated in yeast [87,88], human embryonic kidney (HEK) 293T cells [89][90][91], C. elegans [92][93][94][95], D. melanogaster [96][97][98], zebrafish [99][100][101][102], the mouse [27,[103][104][105][106][107][108][109][110][111][112][113], rat [83,114], sheep [115], pig [116,117] and monkey [118][119][120][121]. Additionally, patient-derived cells were reprogrammed into iPSCs and used to model polyQ diseases [122][123][124][125][126][127][128].…”
Section: Approaches To Modeling Polyq Diseasesmentioning
confidence: 99%
“…Yet, though these models are easy to produce and maintain and provide a convenient basis for experiments, HEK-based models are simplified and lack a full genomic background of the promoter strength, or the full-length gene. HEK 293T cells with polyQ transgenes have been successfully used in drug-screening experiments [91] to analyze the molecular pathways and interactors involved in the pathogenesis of polyQ disease [89], as well as to study trinucleotide expansions [130]. An et al performed a comprehensive analysis of nuclease-based genomeediting methods in HEK 293F cells in 2014 [62].…”
Section: Human Embryonic Kidney 293 Cellsmentioning
confidence: 99%